HUBUNGAN DERAJAT KEPARAHAN ACNE VULGARIS DENGAN BEBAN PSIKOSOSIAL PADA MAHASISWA FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS KATOLIK INDONESIA ATMA JAYA - Fiani Clarissa; Danny Gunawan (Bahasa Indonesia, 2019)
Introduction: Acne vulgaris (AV) is a common dermatological condition among adolescent. Although considered a benign condition and a self-limiting disease, AV can cause psychological problems such as anxiety, depression, and reduce self confidence especially in adolescence because it is a crucial period in psychological and mental development. The purpose of this study is to determine the correlation between AV severity and psychosocial burden on students at Atma Jaya Catholic University of Indonesia School of Medicine and Health Sciences (FKIK UAJ). Methods: This research is an analytic descriptive study with cross sectional method. Sample of this study consist of 141 active preclinic male students at FKIK UAJ year 2016, 2017, and 2018. AV severity was determined by Global Acne Grading System (GAGS). Cardiff Acne Disability Index (CADI) questionnaire was used to measure psychosocial burden caused by AV in the past month. This data was analyzed using Spearman correlation test with significant p<0,05. Results: The prevalence of AV is 100% with 74 respondent (52,5%) in mild severity. The prevalence of psychosocial burden is 86,5% with 96 respondent (68,1%) has little effect on psychosocial burden. There is a positive correlation with weak strength correlation between AV severity and psychosocial burden (p=0,397). Conclusion: There is a correlation between AV severity and psychosocial burden at FKIK UAJ